Neutral Lipophilic Palladium(II) Complexes and their Applications in Electrocatalytic Hydrogen Production and C‐C Coupling Reactions. Issue 10 (27th February 2020) - Cuzan‐Munteanu, Olesea; Sirbu, Dumitru; Giorgi, Michel; Shova, Sergiu; Gibson, Elizabeth A.; Réglier, Marius; Orio, Maylis; Martins, Luísa M. D. R. S.; Benniston, Andrew C.
Abstract : Three neutral palladium(II) complexes [Pd(Ln )2 ] ( n = 1, 2, 3) containing benzotriazole‐phenolate ligands HL1 = 2‐(2H‐benzotriazol‐2‐yl)‐6‐dodecyl‐4‐methylphenol; HL2 = 2‐(2H‐benzotriazol‐2‐yl)‐4, 6‐di‐tert‐pentylphenol; HL 3 = 2‐(2H‐benzotriazol‐2‐yl)‐4, 6‐bis(1‐methyl‐1‐phenylethyl)phenol were synthesized and characterized by several spectroscopic methods ( 1 H, 13 C NMR, UV‐Visible), ESI mass spectrometry and single‐crystal X‐ray diffraction. The geometry around the palladium(II) centre for each complex is described as distorted square planar. The complexes were tested as potential catalysts for electrochemical proton reduction in DMF using trifluoroacetic acid (TFA). Gas analysis under electrocatalytic conditions at a boron‐doped diamond working electrode confirmed the hydrogen production. After performing similar gas analysis experiments using a working mercury pool electrode, no hydrogen was detected which supports the concept that the active species of the catalytic process are palladium particles formed on the surface of the working electrode. The palladium(II) benzotriazolyl phenolate complexes facilitate the formation of particles for electrocatalytic hydrogen production. Furthermore, the palladium(II) complexes PdL2 and PdL3 were able to catalyse microwave‐assisted Heck and Sonogashira C–C coupling reactions. Abstract : Neutral lipophilic palladium complexes based on benzotriazole‐phenolate ligands can operate as C–C bond coupling catalysts (e.g., Heck, Sonogashira). Alternatively, upon electroreduction in DMF containing TFA, they form palladium particles which can produce hydrogen gas by proton reduction.